Social distance and ideological congruence between MPs and citizens: Iberian Legislatures before and after the Great Recession - Freire, A.; Coller, X. (Iberian Legislatures in Comparative Perspective, 2019)
This chapter looks at descriptive and substantive representation in the Iberian Legislatures in comparative perspective. First, we want to study comparatively descriptive representation in Portugal and Spain since the democratic transition until now, with a special emphasis on the period before and after the Great Recession. In this part, we will analyse also the levels of resemblance of the two national legislatures (overall and by parties), vis-à-vis their respective electorates, in terms of socio-demographic characteristics (gender, age, education and profession). MPs’ turnover rates in the two parliaments across the different elections will also be analysed. If data allow it, we will use the Synthetic Index of Social Disproportion for comparative purposes. In the second part of the chapter, we will analyse how well represented in the national Parliaments are the different political parties in the two countries. Levels of disproportionality, in the transformation of votes into seats, and levels of party system fragmentation, from the electoral (ENEP: Effective Number of Electoral Parties) to the parliamentary level (ENPP: Effective Number of Parliamentary Parties), will be a major focus in this part. Additionally, we will analyse also substantive representation in the two national Parliaments understood as the levels of congruence in ideological left-right self-placement. In terms of data, for part one we will use above all official electoral and parliamentary statistics, as well as bio data on MPs and census data on voters. (Elite and mass) survey data will complement the analysis. For part two, we will rely mainly on elite and mass surveys: for Portugal, similar elite and mass surveys have been conducted by André Freire and his teams in 2008, 2012-13 and 2016-17; for Spain, elite surveys have been conducted by Pablo Oñate (2011) and Xavier Coller (2009-10 and 2017-18, fieldwork still in motion) and all will be used, besides being complemented by mass surveys (by CIS and other companies) with comparable variables (at least in terms of left-right self-placement) in the relevant time points.